Nomogram for predicting post-progression-free survival in patients with recurrent pancreatic ductal adenocarcinoma after radical surgery: a retrospective analysis - Qin, Dailei; Xi, Pu; Huang, Kewei; Jiang, Lingmin; Yao, Zehui; Wei, Ran; Li, Shengping (Frontiers in Medicine, 2024)
Abstract Background: Radical resection is the only curative method for patients with pancreatic adenocarcinoma (PDAC). However, nearly 85% of PDAC patients suffer from local or distant recurrence within five years after curative resection. The progression of recurrent lesions accelerates the mortality rate in PDAC patients. However, the influence of clinicopathological factors on post-progression-free survival (PPFS), defined as the period from tumor recurrence to the timing of the progression of recurrent lesions, has rarely been discussed. The present study aimed to explore the independent prognostic factors for PPFS and construct a nomogram for PPFS prediction. Material and Methods: The 200 recurrent PDAC patients were divided into training and validation groups by leave-one-out cross-validation. The patients’ clinicopathological characteristics were compared through a chi-square test. Meanwhile, these factors were enrolled in the univariate and multivariate COX regression to find the independent prognostic factors of PPFS. Moreover, the Kaplan-Meier survival analysis based on the independent prognostic factors was performed. Finally, we constructed a nomogram model for PPFS prediction, followed by an effectiveness examination. Results: PDAC patients who received multi-agent chemotherapy after surgery showed a longer PPFS than the single-agent chemotherapy group. PDAC patients who received multi-agent chemotherapy after recurrence showed a similar PPFS compared to the single-agent chemotherapy group. Local recurrence with distant metastases, early recurrence, lympho-vascular invasion, higher T stage, and higher N stage predicted shorter PPFS in recurrent PDAC patients. Finally, a nomogram to indicate the progression of recurrent lesions was constructed. Conclusion: Multi-agent chemotherapy is recommended for PDAC patients after surgery. Meanwhile, single-agent chemotherapy also deserves consideration after tumor recurrence. Moreover, the nomogram could be used in PPFS prediction.